Alpha methanol city: IoT-integrated energy independent city concept as a realization of Sustainable Development Goals 2030 - Pramana, Naufal Aulia; Farsyad, Ahmad Farid (Applied Environmental Science, 2025)
Background: Climate change, driven by rising greenhouse gas (GHG) emissions, necessitates innovative approaches to achieve sustainability. Indonesia's energy and industrial sectors are significant contributors to these emissions. Traditional CO₂ mitigation strategies, like reforestation, face limitations due to land and time requirements. Thus, technological solutions are critical to address the urgent climate crisis. Methods: This study introduces the Alpha Methanol City (AMC) concept, integrating direct air capture-carbon recycle society (DAC-CRS) systems with renewable energy sources, specifically solar and wind power, alongside IoT and big data technologies. Data were collected through an extensive literature review, analyzing advancements in DAC technology, renewable energy and IoT systems. Theoretical and practical insights were synthesized to propose an energy-independent city model. Findings: The AMC concept processes atmospheric CO₂ into methanol, leveraging renewable energy to reduce operational costs and emissions. IoT and smart grid technologies enable real-time monitoring, optimizing energy use and system performance. SWOT analysis highlighted strengths such as environmental impact and energy independence, alongside challenges like high initial costs and technical complexities. The integration of circular economy principles further enhances AMC’s sustainability. Conclusion: AMC presents a transformative model for urban sustainability by addressing CO₂ emissions and promoting renewable energy adoption. With an implementation timeline of approximately ten years, the concept provides a replicable framework for global sustainable urban development. Novelty/Originality of this article:This study uniquely integrates DAC technology with IoT and renewable energy to create a self-sustaining urban environment. By combining carbon recycling, smart energy management, and circular economy principles, AMC offers a holistic solution to climate and energy challenges, positioning it as a groundbreaking model for sustainable cities.